(3TaGA GdeDefjfs - (3Rjf GdYGHOjf Hf eMeO Ydjs
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd bGfhf GdTaGA HETGQGJ MceJg ai GdbQBf GdPi gh JMaI ddeDefjf deG cGf Yde ef CfaS GdYdhe , dCf ehVhYg HOf GdEfSGf hgh CTQa YGde GdCdhGf s
(3BNQgG (B:s
(3eHJhQ hBNQ eGajg aGdeJNP efgG HhQb GdBS hbThQ GdQeGf hKeQI GdWQaG hLhR GdSQh hMfW GdHdhW , hGdYaU ai NQhL GdeYbOI hGdQMe jLdS ajg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B141 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B_ (3GdfLa (B(751) s
Keywords: (3GdWHs